Message from NSPOI Vol.1(2) - Singh, Rita; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
It gives us immense pleasure to forward the second issue of Journal of Nepalese Society of Periodontology and Oral Implantology on the occasion of 4th annual conference of NSPOI going to be held at Gokarna Forest Resort on 23rd and 24th Feb, 2018. We are very proud to say that JNSPOI has improved leaps and bounds in terms of quality of research paper and reports it has been publishing. The success and continuation of the journal depends on the co-operation and continuous effort of periodontists and all Dental Fraternity of Nepal. It is the responsibility of all our members to come together and contribute for the success and prosperity of our journal. We are confident that the regular and timely publication of journal will encourage us in undertaking research project and carryout various studies. Our Heartfelt Congratulations to the editorial team of JNSPOI on its second issue. We are very grateful and extend our gratitude to all the members of the JNSPOI editorial board for their relentless efforts to make this journal published on time. We would like to extend special thanks to Editor-in-chief Dr. Surendra Man Shrestha, Dr. Bhageshwar Dhami, Executive Editor and Dr. Sujaya Gupta, Assistant Executive Editor for their continuous effort to publish this journal.